The impact of EMU on Europe and the developing countries - Wyplosz, Charles (Oxford, England ; New York : Oxford University Press, 2001)
Now that EMU is here and likely to stay, the 'second generation' of research is under way. This volume presents a significant sample of that research and explores questions such as: How do central bankers who used to run their own banks now melt into a single pot? Are labour markets going to shape up? Is the euro becoming a world currency?
"A study prepared for the World Institute for Development Economics Research of the United Nations University (UNU/WIDER)".
Includes bibliographical references and index.
oif 05/08/16
Loan
Keywords: Monetary policy; Europe